Personality differences and user preferences in visual design styles for data storytelling: a work in progress - Mohd Zanan, Muhammad Faris Basheer; Sheikh Abdul Aziz, Madihah (myHCI-UX C/O MYHCI-UX, UTM IBS, 2021)
In recent years, the Information Visualization (InfoVis) tools have improved and benefited many users. Although the available tools have evolved increasingly in terms of general use and usability, they have historically followed a one-size-fits-all model, ignoring user variations, forcing users to adapt to the interfaces and features that are more general with no emphasis on the visual design styles that are appropriate for different groups of users. According to the literature, research on human factors that include users’ characteristics and personality differences, and their visual design preferences for storytelling is scarce. This study aims to investigate the relationship between personality and the users’ preferences in visual design styles for the storytelling of data to make impactful and insightful reports. This paper presents a work-in-progress relating to personality differences based on the Five-Factor Model (FFM) and user preferences with five elements of data storytelling, to produce meaningful reports.